EFEKTIVITAS PADA PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) DI KABUPATEN SEMARANG (Studi Tentang Penanganan Pengaduan Tindakan Kekerasan Terhadap Perempuan dan Anak) - Syaroh, Dwi Mai; Widowati, Nina (Journal of Public Policy and Management Review, 2018)
Violence against women and children is a crucial issue because every year it always increases. Especially in Central Java Province, There are several areas that enter into violent zones of violence against women and children, one of them is Semarang Regency. To ensure the protection and handling of victims of violent acts that increase from year to year at Integrated Service Center for Women and Children Empowerment was established. This study aims to analyze effectiveness at the Integrated Service Centers for Women and Children Empowerment in dealing with violence against women and children in Semarang Regency and to know the inhibiting factor. The method used in this research is descriptive qualitative method. The results of the study show that the effectiveness of Integrated Service Centers for Women and Children Empowerment in dealing with violence against women and children in Semarang Regency has not been effective. This can be proved by three measures of effectiveness that is the achievement of goals, adaptation and integration that have not met the criteria. Inhibiting factors are not achieving effectiveness of Integrated Service Centers for Women and Children Empowerment in dealing with violence against women and children that is lack of infrastructure in handling violence, limited provision of information, lack of coordination with related parties and lack of counseling personnel. Recommendations for this study are Integrated Service Center for Women and Children Empowerment in Semarang Regency need to increase the victim's companion, maximize coordination between management teams, and increase the provision of complaint information on acts of violence